Impact of Prabowo Subianto Figure on the Political Attitudes of First-Time Voters in the Re-nomination of the Indonesian Presidential Candidate 2019-2024 - Amida Hanna (Program Pascasarjana Universitas Negeri Makassar, 2023)
The possibility of Prabowo Subianto's re-nomination as a presidential candidate in Indonesia for 2019-2024 raises questions about whether his figure, having previously lost in the 2014 presidential election, can create a positive attitude among the Indonesian public, especially first-time voters. In addition to perceptions of the figure which is the focus of this research, the media's significant role in shaping the attitudes of first-time voters is also discussed. This study is a quantitative research with primary data obtained from questionnaires of 250 respondents from five universities in Jakarta and Bandung. The research also uses supplementary data through interviews and literature studies. The analysis technique utilizes multiple regression analysis.The results show a significant and positive influence between the figure and media on the attitudes of first-time voters in viewing Prabowo Subianto. The findings reinforce theories of political communication and political culture regarding the role of figures / political actors in shaping public attitudes or opinions with the aid of media reporting.